IN THE SPRING COCOON GROWING SEASON OF 2023, UNDER THE CONDITIONS OF SURKHONDARYA REGION, REVIVAL OF SILKWORM SEEDS AND ORGANIZATION OF HATCHERIES - Normatov Ro‘zibek Jo‘raqul o‘g‘li; Berdiyev Hasan Baxtiyorovich; Boyqulova Mohinur O’rol Qizi (Scholars Digest Publishing, 2023)
Determination of the incubation of silkworm seeds No matter how the seeds are incubated, the appearance of the silkworm should occur when 4-5 (5-6 in the northern regions) leaves from the buds of the mulberry tree are registered. Because if the leaves were not written from the buds, the nutrients contained in the leaves will not be enough. As a result, the leaf cannot be saved, and there is not enough food for adult worms. It is impossible to delay the period of seed revival, since such leaves are coarse and not very nutritious for worms that have emerged from the seed, when there are 7-8 leaves on the shoots of the tree.
Keywords: Silkworm, Seed, revitalization, distribution, hatchery, box, period, true leaf, coarse, leaf, nutritious, seeding, ventilation.